Pengaruh Sosial Media Facebook Pada Penjualan Studi Kasus Pada UMKM Group Wisata Kuliner Pringsewu - Atmaja, I Made Dwiki; Maradona, I Made Suteja; Diana, Komang Tiara Setia (Puslitbang Akademi Relawan TIK Indonesia, 2023)
The current development of technology has enabled many small and medium-sized enterprises (UMKM) marketers, particularly those in the snack food industry, to utilize social media as a means of promotion and sales. This has encouraged UMKM to create accounts on platforms such as Facebook. They actively engage with their customers on social media, hoping that this interaction will boost their product sales. This research aims to describe the activities undertaken by UMKM on Facebook and understand the influence of the Facebook social media platform on UMKM sales in Pringsewu Regency. The sample for this study consists of 160 respondents from culinary UMKM in Pringsewu. The sampling method used was purpose sampling, measured by the Hair formula. The data type is quantitative, and the data source is primary data. The data collection technique involves the use of questionnaires. The data analysis technique includes validity testing, reliability testing, simple regression analysis, and hypothesis testing with the assistance of the SPSS 2.0 for Windows program. Based on the validity test results, the variables are valid because the Kaiser-Meyer-Olkin Measure of Sampling Adequacy (KMO MSA) value for the social media variable (X) is 0.628 > 0.50 with a significance of 0.000, and the sales variable (Y) is 0.683 > 0.50 with a significance of 0.000. The reliability test shows reliable results because the Cronbach's Alpha value exceeds > 0.60. In the simple regression analysis, the regression coefficient for the Facebook social media variable is 0.166. The results of the T-test indicate that the significance value for Facebook social media (X) on sales is 0.045 < 0.05, and the t-value 2.021 > the t-table value 1.975. In conclusion, there is a significant influence of Facebook social media on sales.